Egr2::Cre Mediated Conditional Ablation of Dicer Disrupts Histogenesis of Mammalian Central Auditory Nuclei - Rosengauer, Elena; Hartwich, Heiner; Hartmann, Anna Maria; Rudnicki, Anya; Satheesh, Somisetty Venkata; Avraham, Karen B.; Nothwang, Hans Gerd (PLOS ONE, 2012)
Histogenesis of the auditory system requires extensive molecular orchestration. Recently, Dicer1, an essential gene for generation of microRNAs, and miR-96 were shown to be important for development of the peripheral auditory system. Here, we investigated their role for the formation of the auditory brainstem. Egr2::Cre-mediated early embryonic ablation of Dicer1 caused severe disruption of auditory brainstem structures. In adult animals, the volume of the cochlear nucleus complex (CNC) was reduced by 73.5%. This decrease is in part attributed to the lack of the microneuronal shell. In contrast, fusiform cells, which similar to the granular cells of the microneural shell are derived from Egr2 positive cells, were still present. The volume reduction of the CNC was already present at birth (67.2% decrease). The superior olivary complex was also drastically affected in these mice. Nissl staining as well as Vglut1 and Calbindin 1 immunolabeling revealed that principal SOC nuclei such as the medial nucleus of the trapezoid body and the lateral superior olive were absent. Only choline acetyltransferase positive neurons of the olivocochlear bundle were observed as a densely packed cell group in the ventrolateral area of the SOC. Mid-embryonic ablation of Dicer1 in the ventral cochlear nucleus by Atoh7::Cre-mediated recombination resulted in normal formation of the cochlear nucleus complex, indicating an early embryonic requirement of Dicer1. Quantitative RT-PCR analysis of miR-96 demonstrated low expression in the embryonic brainstem and up-regulation thereafter, suggesting that other microRNAs are required for proper histogenesis of the auditory brainstem. Together our data identify a critical role of Dicer activity during embryonic development of the auditory brainstem.